Mixed Convective flow over a Stretching Surface with variable thermal conductivity and Binary Chemical reaction - ANURADHA, S.; PRIYA, M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A coupled nonlinear boundary value problem arising from a mixed convective flow of a non-newtonian Casson fluid at a stretching surface with variable thermal conductivity and Binary chemical reaction is investigated in this paper. Using a similarity transformation, the governing equations are transformed into a system of coupled, nonlinear ordinary differential equations and the Numerical solutions for the velocity, temperature and concentration fields are obtained via a bvp4c MATLAB solver. The characteristics of the velocity, temperature and concentration fields in the boundary layer have been analyzed for several sets of values of the Hartman number, the Prandtl number, the Eckert number, the thermal and Mass Grashof number, the temperature relative parameter, Activation energy, Chemical reaction parameter and the Fitted rate constant. The presented results through graphs and tables reveal substantial effects of the pertinent parameters on the flow, heat and Mass transfer characteristics. The numerical consequences are in suitable settlement with those of results formerly published in the literature.